The Mathematics Learning Process in Using Counting Media in Grade 1 Elementary School Students as an Improvement in Student Understanding - Siyamsih, Dwi (PT. Anagata Sembagi Education, 2024)
The purpose of writing this research is to find out that math learning has an important role in shaping students' understanding and numeracy skills. Teachers use various active learning strategies such as math games, math manipulatives, and creative projects to help students understand math concepts concretely. Students are also invited to see the connection between mathematics and daily life situations. This research uses a qualitative descriptive approach to explain the implementation of innovative learning in student character building in junior high school. The qualitative approach is used to describe naturally observed phenomena and to interpret the meaning behind them. The results of the study Mathematics is a fundamental branch of science, covering concepts such as numbers, counting, algebra, geometry, statistics, and calculus. Using symbols, formulas and rules, mathematics allows us to explain and model phenomena in a wide range of fields, from nature to science, technology and economics. More than just a tool for solving practical problems, math is also a means for the development of logical, analytical, and creative thinking skills.